The death of Caligula : Josephus Ant. Iud. XIX 1-273 - Josephus, Flavius (Liverpool University Press, 2013)
"The emperor Gaius ('Caligula') was assassinated in January A.D.41. Since he was the last of the Julii, and he left no heir, it seemed that the dynasty of Caesar and Augustus was finished. Accordingly, the Republic was restored, but then a coup d'etat by the Praetorian Guard put Claudius in power ... the dramatic events of these few days are a crucial turning-point in Roman history -- the moment when the military basis of the Principate was first made explicit. Tacitus' account has not survived, and Suetonius and Dio Cassisu offer no adequate substitute. Fortunately, the Jewish historian Flavius Josephus chose to insert into his 'Jewish Antiquities' -- as an example of the providence of God -- a detailed narrative of the assassination plot and its aftermath taken from contemporary and well-informed Roman sources. This new edition of T.P. Wiseman's acclaimed Death of an Emperor (his translation and commentary of Josephus' account of Caligula's assassination) includes an updated bibliography, revised introduction, translation and commentary. Appendix 1 on the Augustan Palatine has been completely revised to take account of recent archaeological information."--